Africa’s farmers deserve choices - Njuki, Jemimah; Nsimadala, Elizabeth (2021)
In a few weeks, the United Nations will host the first international Food Systems Summit. The goal is to create a global movement committed to solving the many dietary, economic and environmental problems linked to the way food is produced, sold and consumed today.